Inhibition of thioredoxin A1 from Corynebacterium pseudotuberculosis by polyanions and flavonoids - Eberle, Raphael J. [UNESP]; Kawai, Liege A. [UNESP]; de Moraes, Fabio R. [UNESP]; Olivier, Danilo [UNESP]; do Amaral, Marcos S.; Tasic, Ljubica; Arni, Raghuvir K. [UNESP]; Coronado, Monika A. [UNESP] (Elsevier, 2018)
In pathogens, the thioredoxin system forms part of the defense against oxidative stress and ensures the formation of the proper disulfide bonds to ensure protein function. In Corynebacterium pseudotuberculosis, the role and mechanism of TrxA1 has not been elucidated, but, the significant homology among different Trxs and the conservation of the residues that form their active sites underline the importance of the Trx systems. Proteins involved in redox metabolism and low molecular weight thiols, which might interact with them, become attractive targets to modulate the activity of pathogens. The activity of the protein was investigated using a turbidimetric assay system. The influence of different pH and low molecular weight thiols were tested. Additionally, this assay was used to investigate the inhibitory potential of ligands from different molecular families, such as, polyanions (suramin and heparin) and flavonoids (hesperetin and hesperidin). All four compounds showed inhibition of the protein activity by approximately 80%. The interactions between these compounds and Cp-TrxA1 were investigated using CD spectroscopy, NMR, molecular docking and dynamics. Our results demonstrate that suramin and hesperetin can serve as lead molecules for the development of specific inhibitors for the C. pseudotuberculosis TrxA1.
Keywords: Corynebacterium pseudotuberculosis; Inhibitor; Molecular dynamics; NMR; Thioredoxin